The grief dimensions in Marie Howe’s “What the Living Do” (Passage: Journal of English Language and Literature, 2025)
This paper aims to discuss how grief is being expressed in literary works particularly in contemporary poems.  Grief is a universal feeling that a person felt when facing distressful or traumatic events in life such as the death the loved ones. There are various ways that a person does to deal with grief, one of them is through literature more specifically by writing a poem. One genre in literature which narrates the surviving grievance is called Grief Account. Marie Howe is one of the most prolific contemporary American poets who experience grievance and use her poems to deal with the emotion. One of her poems that best represent the grief account genre is entitled “What the Living Do” which was published in 1997 and is used as the research object of this paper. The concept of Grief Dimensions by Michael Robert Dennis was drawn on to identify and analyse the aspects of grief that are present in the poem. Dennis suggests that there are six grief dimensions namely restorative, evaluative, interpretive, affirmative, affective, and transformative. The analysis was conducted qualitatively by implementing descriptive method as well as formalism approach to examine various grief imageries and symbolisms present in the poem. The paper found that all of Dennis’ six dimensions of grief are present in Howe’s “What the Living Do” which shows how the poem manage to express multiple facets of grievance in multiple ways despite its short length. For future research, it is possible to develop an analysis of poems about grief by other contemporary poets or doing comparative analysis on multiple grief poems from different periods to show whether different temporal contexts influence the way people express their grief through poetry.